Numerical Simulation of Interfacial Fracture Behavior of Heat-Insulating and Abradable Seal Coatings - WANG Xu, SHI Qiusheng, LI Guangrong, YANG Guanjun (Cailiao Baohu, 2024)
In order to explore the failure behavior of heat-insulating and abradable seal coating，the effects of interface roughness and the abradable structure of the surface layer near the interface on the cracking of the composite coating were investigated.The cohesive zone model and the phase-field damage method were used to describe the overall peeling of cracks along the interface and the internal fracture behavior of abradable surface layer.Moreover，the peeling failure mechanism of coating was revealed.Results showed that the bonding strength and cracking tendency of the coating presented opposite change laws with the increase of interface roughness.On the one hand，the effective contact area of the non-damaging composite coating interface increased，and the bonding strength increased.On the other hand，with the increase of roughness，the internal fracture of the surface layer became easier.Therefore，the interface roughness should be optimized reasonably.In addition，the pore of surface layer near the interface could reduce the bonding strength at the interface.Based on this，an appropriate interface roughness was selected，and an anti-cracking compact transition layer was introduced between the thermal insulation layer and the abradable surface layer to eliminate the weakening effect of surface layer pores on the interface strength of composite coatings and design an anti-cracking coating.